Evaluation of a Company’s Investment Attractiveness by The Example of MOSTOTREST PJSC ("Journal "U". Economy. Management. Finance.", 2020)
The article considers the indicators of liquidity of assets, financial stability and profitability of the company. The analysis is carried out and a three-component indicator is compiled. The dynamics of indicators for 3 years is considered. Changes are analyzed and possible risks are assessed for the company in the field of reducing net profit and cost growth. On the example of Mostotrest PJSC, the dynamics and significance of the indicators are shown, and the results that contribute to the adoption of a positive investment decision are described. Recommendations are given for resolving financial problems that have arisen.
Keywords: financial analysis; liquidity ratios; Mostotrest PJSC; investment decision; profitability